Crystal structure of Plasmodium vivax FK506‐binding protein 25 reveals conformational changes responsible for its noncanonical activity. Issue 7 (26th December 2013) - Rajan, Sreekanth; Austin, David; Harikishore, Amaravadhi; Nguyen, Quoc Toan; Baek, Kwanghee; Yoon, Ho Sup
Abstract The malarial parasites currently remain one of the most dreadful parasites, which show increasing trend of drug resistance to the currently available antimalarial drugs. Thus, the need to identify and characterize new protein targets in these parasites can aid to design novel therapeutic strategies to combat malaria. Recently, the conserved FK506‐binding protein family members with molecular weight of 35 kDa from Plasmodium falciparum and Plasmodium vivax (referred to as PfFKBP35 and PvFKBP35, respectively) were identified for drug targeting. Further data mining revealed a 25‐kDa FKBP (FKBP25) family member present in the parasites. FKBP25 belongs to a unique class of FKBP, because it is a nuclear FKBP with multiple protein‐binding partners. Apart from immune regulation, it is also known for its chaperoning role in various cellular processes such as transcription regulation and trafficking. Here, we present the biochemical characterization and 1.9‐Å crystal structure of an N‐terminal truncated FKBP25 from P. vivax (PvFKBP2572–209). The protein reveals the noncanonical nature with unique structural changes observed in the loops flanking the active site, concealing the binding pocket. Further, a potential calmodulin‐binding domain, which is absent in human FKBP25, is observed in this protein. Although the functional implication of Plasmodium FKBP25 in malaria still remains elusive, we speculate that the notable conformational changes in its structure might serve as an overture in understanding its molecular mechanism. Proteins 2014; 82:1235–1244. © 2013 Wiley Periodicals, Inc.